Case report: Granzyme-B expression by T- and B- cells during severe AQP4-positive Neuromyelitis Optica spectrum disorder with fatal venous thromboembolism outcome - Boldrini, Vinícius Oliveira; Brito, Mariana Rabelo; Quintiliano, Raphael Patrício Silva; Scárdua Silva, Lucas; Yasuda, Clarissa Lin; Cendes, Fernando; Farias, Alessandro Santos; Damasceno, Alfredo (Frontiers in Neurology, 2023)
Background: The expression of serine protease granzyme-B (GzmB) by circulating CD8+ T lymphocytes has been recently suggested as a biomarker for poor immunotherapy response and severe disability in patients with Neuromyelitis Optica spectrum disorders (NMOSD). In parallel, venous thromboembolism (VTE) has been reported mainly in NMOSD patients exhibiting transverse myelitis. Case presentation: Here, we describe an Aquaporin-4 positive (AQP4-positive) NMOSD patient who showed short myelitis (SM) and experienced a fatal pulmonary thromboembolism/lower extremity deep vein thrombosis during anti-CD20 treatment. Flow cytometry analyses from the peripheral blood revealed an enhanced cytotoxic behavior through circulating CD8+GzmB+ T, CD4+GzmB+ T lymphocytes, and residual CD19+GzmB+ B cells. Conclusions: Fatal VTE may be a rare outcome, particularly in patients exhibiting SM, and may share poorly understood immunological mechanisms with AQP4-positive NMOSD severity.